Case Report: Bronchogenic Cyst in the Right Atrium of a Young Woman - Fukudome, Yuya; Hieda, Michinari; Masui, Shiho; Yokoyama, Taku; Futami, Shutaro; Moriyama, Shohei; Irie, Kei; Fukata, Mitsuhiro; Ushijima, Tomoki; Shiose, Akira; Akashi, Koichi (Frontiers in Cardiovascular Medicine, 2022)
A 31-year-old woman was referred to our hospital for evaluation of a cardiac mass in the right atrium. Cardiac magnetic resonance imaging indicated a cystic mass filled with fluid accumulation in the right atrium. The mass was identified as a cardiac cyst and was surgically removed. Pathological examination revealed an extremely rare bronchogenic cyst. Bronchogenic cysts are benign congenital abnormalities of primitive foregut origins that form in the mediastinum during embryonic development. There is unusual clinical dilemmas surrounding the treatment plan for cardiac surgery or biopsy of cardiac masses, especially in patients with rare cardiac cysts. The anatomical location of the cyst can be related to various clinical symptoms and complications. In cases of indeterminate cardiac cysts, direct cyst removal without prior biopsy is of utmost importance.